DENTISTS' KNOWLEDGE AND EXPERIENCE REGARDING LEPROSY IN AN ENDEMIC AREA IN BRAZIL - Martins, Ronald Jefferson; Carloni, Maria Emília Oliveira Gomes; Moimaz, Suzely Adas Saliba; Garbin, Cléa Adas Saliba; Garbin, Artênio José Ísper (FapUNIFESP (SciELO), 2016)
This study aims to analyze the dental surgeons' knowledge about leprosy and its ways of transmission, clinical characteristics and treatment, besides analyzing their experience with respect to diagnostic suspicion and case referrals. The study population comprised 242 dental surgeons working in the public dental service of the city of Cuiabá, Mato Grosso, Brazil. A self-applicable questionnaire containing questions about the dental surgeon's profile was used, including his/her knowledge on leprosy, as well as his/her practices concerning the disease. The results showed a predominance of female dental surgeons (65.7%), with ages ranging between 30 and 39 years old (43%) and professionals having six to 10 years of experience since graduation. Concerning their time working in the Unified Health System (SUS), the highest percentage of dental surgeons referred more than 10 years. Regarding the knowledge about the disease, 30.6% did not know the efficacy of the treatment of leprosy, 47% did not know the disease had to be notified compulsorily and only 8.3% had received information about leprosy at work. Besides that, most of them mentioned feeling little security when treating patients with leprosy (61.6%). Thus, dental surgeons' deficient knowledge on issues related to leprosy may be highlighted.